2016
DOI: 10.1016/j.jaci.2015.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation markers overexpressed specifically in patients with aspirin-exacerbated respiratory disease

Abstract: Peripheral platelets were activated more in patients with stable AERD compared with those in patients with stable ATA, patients with idiopathic chronic eosinophilic pneumonia, and control subjects. Platelet activation was involved in cysteinyl leukotriene overproduction and persistent airflow limitations in patients with AERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 48 publications
5
55
0
1
Order By: Relevance
“…Recently, novel mechanisms have been proposed, such as systemic inflammation, aberrant functions of platelets and overexpressed platelet activation242526. Aspirin challenge, for instance the ASA-BPT, is the gold standard for confirming aspirin hypersensitivity, however, there are still risks for bronchospasm as well as various contraindications27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, novel mechanisms have been proposed, such as systemic inflammation, aberrant functions of platelets and overexpressed platelet activation242526. Aspirin challenge, for instance the ASA-BPT, is the gold standard for confirming aspirin hypersensitivity, however, there are still risks for bronchospasm as well as various contraindications27.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets contribute to the pathogenesis of AERD through various pathways, including the formation of platelet-leukocyte aggregates, abnormal function of platelets in vitro and overexpression of platelet activation252636. After platelet activation, intracellular S1P is released into the environment3738.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, platelet MPs in plasma were reported to be significantly increased in subjects with asthma, which is one of the triad of conditions defining AERD 62 . Although growing evidence has suggested that abnormal platelet activation is uniquely associated with the pathophysiology of AERD independently of asthma 23, 24 further studies are necessary to clarify this point. However, PltMP levels in NLFs were higher in AERD than in CRSwNP with aspirin tolerant asthma, and the multivariate logistic analysis showed our cut-off values of platelet MPs, epithelial MPs, and mast cell MPs were significantly associated with AERD independently of asthma in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that some MP types, especially EpCAM+EpiMPs, PltMPs, and AV+MCMPs, are potential biomarkers for distinguishing AERD from CRSwNP in the clinic. Although platelet activation markers were reported to be potential diagnostic biomarkers for AERD in blood 23 , MP analysis in NLF may make diagnosis of AERD more robust by evaluating both EpiMPs and AV+MCMPs in addition to PltMPs. Recently, type 2 innate lymphoid cells have been detected in nasal polyp tissues and interest has focused on their role in the pathophysiology of CRS 64, 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation